Vernacular Qur'anic Interpretation in Gorontalo: Local Wisdom and Linguistic Strategies - Naelul Huda, Ade; Fitriana, Muhammad Azizan; Lubis, Muhammad Riyadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study investigates the process of vernacularization in the Gorontalo language translation of the Qur’an published by the Gorontalo Regional Government. Situated within the broader academic debate on postcolonial and decolonial Islamic hermeneutics, the research addresses how local languages and cultural frameworks participate in shaping religious meaning and resisting Arab-centric epistemic authority. Employing a qualitative methodology with a library research approach, the study utilizes descriptive analysis to examine textual elements in the translation. The findings reveal three major categories of local cultural integration: (1) lexical absorption—Arabic-derived terms adapted into Gorontalo, such as na'ale, aba/baaba, helidu, and sap; (2) linguistic politeness—refined expressions like waatia, yo'i, ti, and te that reflect local norms of respect; and (3) cultural expressions—idioms and metaphors such as Tabia, Ta ilahula, and Dulahu momooli, which encode Gorontalo cosmology and spiritual values. Theoretically, this research contributes to the discourse on vernacular Qur’anic interpretation by demonstrating that translation is a culturally embedded and ideologically charged act. It affirms the significance of local hermeneutics in constructing religious knowledge and challenges epistemic centralization by legitimizing vernacular voices within Islamic interpretive traditions.